The Influence of Character and Personality Education on Students' Confidence Levels: The Importance of Coaching and Continuity in Education - Maryanah Maryanah (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze the effect of character and personality education on students' self-confidence levels and emphasizes the importance of coaching and continuity in education. This study uses a quantitative method with a descriptive analysis approach. The data used are primary. Data were collected using research instruments. The research subjects were D3 Midwifery students in the first semester. Based on the results of data and analysis, it can be concluded that most of the D3 Midwifery students in the first semester of Health Polytechnic have a sufficient level of confidence, meaning that midwifery students still need to develop self-confidence through continuous coaching and guidance so that they have confidence. Especially in decision making and relationships with patients and the community.